Man and the typology of divine blessings with emphasis on the verses of Surah Al-Rahman - Hossein Hosseini Bojdani; Mehdi Mehrizi Tariqi; Seyed Mohammad Bagher Hojjati (پژوهش نامه معارف قرآنی, 2020)
Due to having innate traits and characteristics,human beings have been the focus of attention of rationalists, and every thinker has analyzed human cognition according to his own vision;Onthe other hand, understanding the blessings created is the surest way to know the Creator of the universe, and by knowing the Creator,the nature of man is explained,which in turn will cause gratitude,reminder of man,liberation from neglect,and finally open the way to worldly happiness and the hereafter. It reveals the human and divine blessings around man.Surah Al-Rahman emphasizes the blessings of God in particular and divides the blessings of God into two categories: worldly and hereafter.He mentioned the creation of plants and their products, paying attention to the nature and manner of human creation,placing the seasons of the year and using the seasons, using the seas and marine products, the perishability of possible existence and the inevitable immortality of existence, and so on.Auditing, the blessings of the collapse of the world order and the absolute quality of God, the creation of conditions for the resurrection, the establishment of justice and the implementation of the law of divine justice for sinners, the creation of paradise and divine gifts to believers,sustainable and eternal life, other heavenly blessings including gardens, springs and beauties Wafa considered Hourian Beheshti as one of the blessings of the Hereafter.Therefore, this article tries to deal with human beings and divine blessings from the Quran's point of view with an analytical-descriptive approach,emphasizing the verses of Surah Ar-Rahman.